2018
DOI: 10.1111/odi.12943
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of SNPs in RAD51 and XRCC3 in oral and oropharyngeal carcinomas

Abstract: Combined effects of RAD51 (rs1801320 and rs1801321) and XRCC3 (rs861539) SNPs with environmental carcinogens (tobacco and alcohol) are associated with oral and oropharyngeal SCC development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, a large number of population-based studies reported an association between the studied variant and disease risk. Synergistic effects of the risk alleles of some SNPs with environmental factors on the susceptibility to such diseases were also reported in several studies [ 76 , 77 ]. Point mutations have been introduced as a source of de novo genetic diseases [ 78 ].…”
Section: Clinical Significance Of Snp Mutationsmentioning
confidence: 55%
“…Interestingly, a large number of population-based studies reported an association between the studied variant and disease risk. Synergistic effects of the risk alleles of some SNPs with environmental factors on the susceptibility to such diseases were also reported in several studies [ 76 , 77 ]. Point mutations have been introduced as a source of de novo genetic diseases [ 78 ].…”
Section: Clinical Significance Of Snp Mutationsmentioning
confidence: 55%
“…According to the inclusion and exclusion criteria, ten papers involving a total of 2484 controls and 2377 cases were enrolled in our analysis after selection [29, 3139]. The progress of paper selection is demonstrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…To date, a variety of articles have been conducted to assess the correlation between the RAD51 gene polymorphisms and the risk of HNC and EC [2939]. However, the results are still inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the authors concluded that the genetic variability of XRCC3 and/or RAD51 genes might be of relevance with respect to HNC risk. The effects of SNPs in RAD51 and XRCC3 on susceptibility to oral and oropharyngeal squamous cell carcinomas (SCC) and their clinicopathological significance were recently reported by Santos et al (Santos et al, 2019). Specifically, SNPs 135GNC (rs1801320) and 172GNT (rs1801321) in RAD51, and T241M (rs861539) in XRCC3 were genotyped in 81 patients presenting oral SCC, 45 presenting oropharyngeal SCC, and 130 healthy controls.…”
Section: Head and Neck And Oral Cancermentioning
confidence: 99%